2021
DOI: 10.1155/2021/1755140
|View full text |Cite
|
Sign up to set email alerts
|

The Groundwater Geochemistry and the Human Health Risk Assessment of Drinking Water in an Area with a High Prevalence of Chronic Kidney Disease of Unknown Etiology (CKDu), Sri Lanka

Abstract: Chronic kidney disease of unknown etiology (CKDu) has become an alarming health issue in Sri Lanka. The disease is more notable among farming communities and people who consume groundwater as their main source of drinking water. To assess the possible links between drinking water chemistry and expansion of CKDu, the study was compared with hydrogeochemical data of drinking water sources in a CKDu prevalent area (Girandurukotte GND, Badulla District) and a reference area (Dambethalawa GND, Ampara District) in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 102 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…The wisdom behind this is that it will allow spatial assessment of the disease aetiology in the area since the majority of the previous studies implicated environmental compounds and factors for the disease epidemics. It has been reported that the distribution of environmental nephrotoxic compounds such as cadmium and Arsenic can be influenced by various confounding factors, including local geology, as well as anthropogenic activities (Botheju et al, 2021). Thus, cross-mapping the disease incidence location to identify hotspots as well as surrounding area environmental factors assessment is critically crucial.…”
Section: Discussion the Missing Content And Methodological Gap Of The...mentioning
confidence: 99%
See 1 more Smart Citation
“…The wisdom behind this is that it will allow spatial assessment of the disease aetiology in the area since the majority of the previous studies implicated environmental compounds and factors for the disease epidemics. It has been reported that the distribution of environmental nephrotoxic compounds such as cadmium and Arsenic can be influenced by various confounding factors, including local geology, as well as anthropogenic activities (Botheju et al, 2021). Thus, cross-mapping the disease incidence location to identify hotspots as well as surrounding area environmental factors assessment is critically crucial.…”
Section: Discussion the Missing Content And Methodological Gap Of The...mentioning
confidence: 99%
“…Essentially, this issue of heavy metals exposure needs to be carefully examined since the local population sourced and used water from shallow boreholes and wells that are suspected to be contaminated with agrochemicals in the area. It has been highlighted in the literature that one or more of these trace elements and their synergies induces renal damage as reported byWasana et al (2017) andBotheju et al (2021).…”
mentioning
confidence: 86%
“…The heavy metal concentrations in the mixture were decided based on the highest reported contamination of drinking water sources in CKDu prevalent areas. 35,36 The membrane was then dipped in 30 ml of food grade vinegar solution for 1 hour and washed with deionized water several times. The recycled membrane was then used in the subsequent adsorption of cation mixtures.…”
Section: Simultaneous Adsorption Of Total Hardness As(v) Cd(ii) and P...mentioning
confidence: 99%
“…First is as a result of the ineffective control of infectious, re-emerging, and newly emerging diseases; second is due to the rise of chronic diseases into the top five list of catastrophic disorders as a result of demographic and nutritional transitions; and lastly because of the steady increase in the incidence of trauma and injuries [ 7 ]. In addition, the influence of environmental factors also needs to be considered in the progression of CKD, especially the clean water source which could contribute to the waterborne diseases and diarrheal illnesses leading to acute kidney injury (AKI), schistosomiasis that can cause CKD, and water pollution that further causing CKD [ 8 , 9 ].…”
mentioning
confidence: 99%